Comparison of First Year Growth Among Field, Hatchery- and Laboratory-Raised Juvenile Red King Crab, Paralithodes camtschaticus (Tilesius, 1815), in Alaska. Issue 3 (1st May 2014) - Westphal, Miranda J.; Eckert, Ginny L.; Tamone, Sherry L.
Abstract: In an effort to better understand juvenile growth in the first year and to determine potential effects of hatchery larval rearing, we compared growth of juvenile red king crab, Paralithodes camtschaticus (Tilesius, 1815 ), in the field and under laboratory-rearing conditions. Glaucothoe were obtained from the Alutiiq Pride Shellfish Hatchery and field; once molted to first stage juveniles, both sets were raised individually in the laboratory under ambient conditions (hereafter called hatchery/laboratory-reared and wild/laboratory-reared, respectively) and measured at each molt. Field-surveyed juveniles were observed and measured monthly in the intertidal in Juneau, AK, USA. Size, molt interval, cumulative molt interval, and molt increment did not differ significantly between hatchery/laboratory-reared and wild/laboratory-reared crab or between male and female crab over one year. Crab reached an average ${\rm size} ± {\rm SD}$ of $13.6 ± 2.1 \, {\rm mm \, CL}$ after 10-11 molts/year with 24% average molt increment at ambient temperatures. Carapace lengths of hatchery/laboratory-reared, wild/laboratory-reared, and field-surveyed juveniles were not significantly different in five of eight months from January through August, with small differences in January, February, and May, likely resulting from differences in hatch timing. Spine lengths differed from January through March but not from April through August. Spine lengths of hatchery/laboratory-reared crab were significantly larger than field-surveyed crab from January through March. Wild/laboratory-reared crab had significantly longer spine lengths than field-surveyed crab in February and March. In conclusion, growth did not differ significantly among juveniles reared in the laboratory and from the field.